ANALISIS KOMUNIKASI, KOMPENSASI FINANSIAL DAN NON FINANSIAL YANG MEMPENGARUHI KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI INTERVENING DI PT BANK TABUNGAN PENSIUNAN NASIONAL PURNA BAKTI WILAYAH JEMBER - Dwi Fajar Ardiyanto; Mohammad Saleh; Diana Sulianti K. Tobing (RELASI : JURNAL EKONOMI, 2014)
This study aimed to analyze the effect of communication on the Organizational Commitment, financial compensation on Organizational Commitment, Non Financial Compensation on Organizational Commitment communication on employees performance, financial compensation on employees performance, non financial compensation on employees performance, and analyze the effect Organizational Commitment on Employees Performance at PT Bank Tabungan Pensiunan Nasional Purna Bakti Region Jember. This research study is categorized as an explanation (explanatory research) or research causal (causal research), because this study intends to clarify the causal relationship (cause and effect) between variables by testing the hypothesis that has been formulated with samples Simple Random Sampling technique is based on the number of employees Broiler Farms as many as 110 people. Based on these tests it can be stated that the compensation financial (X2)has the greatest total effect on Employees Performance (Y) in PT Bank Tabungan Pensiunan Nasional Purna Bakti Region Jember.